Effect of Water Proofing Materials on Self-Healing Concrete (European Journal of Formal Sciences and Engineering, 2020)
Improving the strength of the concrete structures and increasing the service life is an important issue. The service times of the concrete remained; external factors such as water penetrating into these micro-cracks and shorten the life of the concrete. In order to solve this problem, the idea of self-healing concrete with bacteria or other materials has been put forward and studies have shown that using CaO based materials that repair cracks in this direction by precipitating calcite. It is obvious that long term performance of concrete will increase with to prevent water pass to concrete interior. Instead of forming a barrier on the positive or negative side of concrete, water proofing admixture turn the concrete itself into a water barrier. Internal concrete waterproofing systems can be water repellents or crystalline admixtures. In this study, water proofing admixture was added to concrete mixture as water proofing material and its effect on self-healing in terms of filling the pores was investigated. Beam samples including the CaO based water proofing powder materials were produced in size of 285x75x25 mm. The samples were cracked in the flexural machine. After some days, the cracks were investigated by microscope. Crak control was continued till 28 days. At the end of study, the cracks smaller than 0.3 mm were self-healed. However, the bigger cracks than 0.3 mm cannot be self-healed by water proofing material. Consequently, self-healing of concrete with CaO based water proofing powder material is very promising for the environmentally friendly and sustainable structures of the future.